If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + -5 = (x + -1) Reorder the terms: -5 + -5x = (x + -1) Reorder the terms: -5 + -5x = (-1 + x) Remove parenthesis around (-1 + x) -5 + -5x = -1 + x Solving -5 + -5x = -1 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -5 + -5x + -1x = -1 + x + -1x Combine like terms: -5x + -1x = -6x -5 + -6x = -1 + x + -1x Combine like terms: x + -1x = 0 -5 + -6x = -1 + 0 -5 + -6x = -1 Add '5' to each side of the equation. -5 + 5 + -6x = -1 + 5 Combine like terms: -5 + 5 = 0 0 + -6x = -1 + 5 -6x = -1 + 5 Combine like terms: -1 + 5 = 4 -6x = 4 Divide each side by '-6'. x = -0.6666666667 Simplifying x = -0.6666666667
| cos34=8/x | | 2/3x5/12 | | (3v-8)(3+v)=0 | | -X+4x+7=2x+5 | | 10(-6x+3)=-510 | | -243=-9(10+6) | | 3x-12+3x=x+3 | | N^3-3n/3n | | 9x(4+4)= | | 4x/5÷15/5x | | x+.05x=6.67 | | 0.6-5=0.1+7 | | 5x+16=2x+37 | | 4x^3-28x^2-32x=0 | | 4x^3-3x^2+4=0 | | 6+2=412 | | 121=-3(7-7n)-5 | | 5.71x+100=32.6041+10x | | 2x^2+3x^2-12x+1=0 | | 84=7(6-x) | | 5/6x-7/6=7 | | .25x+.8y=8.65 | | 6/8=y/12 | | 4-2 x=1 | | w+0.82=1.17 | | sqrt(x^2+12x-180)=0 | | (81)^(1/4) | | 3-7(5v-5)=318 | | 5-2(x-1)=3(2-x)+7 | | 7x^2-60x=0 | | 3-5x-4+7x=4x-2x+1 | | (3/11)/(2/3) |